Analisis Manfaat Ekonomi Rencana Pelebaran Jembatan Mangunharjo Kota Madiun Ditinjau Dari Sisi Lalu Lintas: Analysis Of The Economic Benefits Of The Mangunharjo Bridge Widening Plan In Madiun City From The Traffic Perspective - Jawara, Kholiddien Tyas; Ansusanto, J. Dwijoko (Media Ilmiah Teknik Sipil, 2025)
The Manguharjo Bridge has a traffic width of 6.50 m (two lanes in two directions) and is prone to congestion due to high traffic flow and limited road capacity. Congestion causes economic losses, environmental pollution, and energy waste. The Madiun City Government has proposed widening the bridge to address these issues. Based on this overview, a study is needed to assess the economic benefits of the Manguharjo Bridge widening plan. This research uses a quantitative methodology to analyze the benefits of widening the Manguharjo Bridge with two alternative lane widths over the bridge's 75-year lifespan. Primary data includes geometric surveys, traffic volume, and land use. Secondary data includes vehicle growth, time value, and vehicle component prices. Traffic performance analysis uses PKJI 2023, traffic forecasting, Vehicle Operating Cost and time value savings to evaluate the project's benefits. Based on the analysis results, Alternative 1 yields Vehicle Operating Cost savings of IDR 1,504,929,465,276 and time value savings of IDR 8,672,188,817,959. Alternative 2 achieved Vehicle Operating Cost savings of Rp3,903,545,756,479 and time value savings of Rp9,852,675,485,931. The results of the above analysis show that Alternatives 1 and 2 have good economic efficiency, which will be used for evaluation in determining the width of the traffic lanes on the Manguharjo Bridge.